Seismic response analysis of multidrum classical columns. - Konstantinidis, Dimitrios
This paper presents a numerical investigation on the seismic response of multidrum classical columns. The motivation for this study originates from the need to understand : (a) the level of ground shaking that classical multidrum columns can survive and (b) the possible advantages or disadvantages of retrofitting multidrum columns with metallic shear links that replace the wooden poles that were installed in ancient times. The numerical study presented in this paper is conducted with the commercially available software Working Model 2D, which can capture with fidelity the sliding, rocking and slide rocking response of rigid body assemblies. This paper validates the software Working Model by comparing selected computed responses with scarce analytical solutions and the results from in-house numerical codes initially developed at the University of California, Berkeley, to study the seismic response of electrical transformers and heavy laboratory equipment. The study reveals that relative sliding between drums happens even when the g-value of the ground acceleration is less than the coefficient of friction, u, of the sliding interfaces and concludes that : (a) typical multidrum classical columns can survive the ground shaking from strong ground motions recorded near the causative faults of earthquakes with magnitudes Mw=6.0-7.4; (b) in most cases multidrum classical columns free to dislocate at the drum interfaces exhibit more controlled seismic response than the monolithic columns with the same size and slenderness; (c) the shear strength of the wooden poles has a marginal effect on the sliding response of the drums; and (d) stiff metallic shear links in between column drums may have an undesirable role on the seismic stability of classical columns and should be avoided.
Keywords: Multidrum classical columns; Sliding; Rocking; Seismic response; Earthquake engineering